Psychosocial Conditions of Parents with Premature and Low Birth Weight Infants in Developing Countries: Scoping Review - Winanti, Della; Septiana Pratiwi, Cesa; Koni Suryaningsih, Endang (Universitas Muhammadiyah Surakarta, 2025)
Premature and low birth weight (LBW) infants will increase the risk of mortality, morbidity, and disability, resulting in psychological distress felt by parents. The purpose of this scoping review is to map published articles related to the psychosocial conditions of parents who have premature and LBW infants, especially in developing countries. This study employed PCC Framework (Population, Concept and Context), Prisma ScR checklist, 3 databases (PubMed, Wiley Online Library, Taylor & Francis) and 1 gray literature (Research Rabbit), published from 2019-2024, in English, original articles, free full text, articles from developing countries and used quantitative and qualitative methods. This study used the keywords “Parents” AND “Low birth weight” OR “Psychological wellbeing” OR “Parental stress” OR “Psychosocial health” AND “Developing Countries”. This scoping review used JBI Critical Appraisal Tools such as the Checklist for Analytical Cross-Sectional and Qualitative Research. Of the 1,939 articles selected through the Prisma Flowchart and Critical Appraisal using the Joanna Briggs Institute (JBI), 9 articles were found suitable. This study focused on social support provided to parents to reduce psychological problems and disorders and improve quality of life. This study highlights the importance of parents’ support in preterm and LBW infants in developing countries, in order to minimize their psychological problems and disorders. The author suggests that the use of a qualitative research method for the next research should be applied to explore the psychological conditions of fathers who have premature and LBW infants in developing countries comprehensively.